Analisis Strategi E-Marketing Dalam Upaya Peningkatan Penjualan Travel Agent Online mybaliwisata.com - Fitria Pebri Evariyanti; Ni Made Estiyanti; Sephy Lavianto (Journal of Applied Informatics and Computing, 2019)
Every year the graph of foreign and domestic tourist arrivals to Bali continues to increase. This is a great opportunity to increase tourist destination visits to Bali. The role of technology will answer the problems that exist in this era of globalization by using computerized systems, so that the use of information technology helps effectiveness and efficiency in working on information system processes. After analyzing the Business Model Canvas (BMC) and E-marketing Business data using social media, the results obtained were an increase in sales of mybaliwisata.com online travel agents in increasing sales turnover. This study uses the Break Event Point (BEP) analysis method to calculate the valuation of mybaliwisata.com online travel agent company, so that optimization of the increase in mybaliwisata.com Travel Agent Online sales can be done well.